Strategi Pengembangan Kawasan Wisata Sejarah Monumen Kresek Terintegrasi Agrowisata Berbasis Community-Based Tourism (CBT) di Kabupaten Madiun - Soebijantoro, Soebijantoro; Hartono, Yudi; Huda, Khoirul (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
This research aims to reveal the development of the Kresek Monument historical tourism area for agrotourism based on Community Based Tourism. Qualitative descriptive research method. Data collection through observation, interviews, focus group discussions, and document study. Data validity through source triangulation. Analyze data with interactive analysis. The results of the research show that the Kresek Monument historical tourist area needs to be developed with a new perspective that the landscape of the Kresek Monument historical tourist area has the potential to become a beautiful natural tourist destination. For a long time, the community has been actively involved in developing the Kresek Monument historical tourist area through the "Mekar" Tourism Awareness Group. The community took the initiative and tried to integrate it with agrotourism around the monument area. Since the COVID-19 pandemic, the management of the Kresek Monument historical tourist area has been completely taken over by the Madiun Regency Tourism, Youth and Sports Department, while day-to-day management is carried out by the Madiun Regency Environmental Service. The Kresek Village Government is also involved in management through the Kresek Village Village-Owned Enterprise. Residents are involved based on assignments from these parties, such as tour guides. There is no policy synergy between stakeholders, which is a challenge in developing the Kresek Monument historical tourism area which is integrated with the community's agro-tourism area. The community is also faced with technical obstacles in the field in the form of road infrastructure connecting the Kresek Monument historical tourist area with unsupported agro-tourism areas.